Pengaruh Ukuran Perusahaan, Profitabilitas, dan Kebijakan Hutang terhadap Nilai Perusahaan - Probo Anugrah; Ahmad Idris; Trisnia Widuri (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to determine the relationship between firm size, profitability, and debt policy on company value at PT. KMI Wire and Cable, Tbk. for the 2017–2024 period. Company value is the main focus because it reflects the company’s overall performance and can attract investor interest and perception. Firm size is measured by the natural logarithm of total assets (LN), profitability is measured by return on equity (ROE), debt policy is measured by debt-to-equity ratio (DER), and company value is measured by price-to-book value (PBV). This research employs a quantitative method using multiple linear regression analysis to examine the causal relationship between variables. The data used are secondary data in the form of quarterly financial reports of PT. KMI Wire and Cable, Tbk. during the study period. The results of the study indicate that firm size has a negative and significant effect on company value, while profitability and debt policy show a positive and significant effect. Simultaneously, firm size, profitability, and debt policy jointly have a positive and significant effect on company value. These findings highlight the importance of balancing company growth with efficient asset management and optimal capital structure to ensure long-term financial stability. Moreover, the study contributes to empirical evidence supporting Trade-Off Theory and Pecking Order Theory, showing how capital structure decisions and profitability management can shape investor perception and firm valuation. This study provides practical insights for management in designing strategies to optimize capital structure, strengthen profitability, and manage debt responsibly to enhance firm value and investor confidence.